A BRIEF STUDY OF THE IMPACT OF THE FINANCIAL CRISIS OF 2008 ON THE FISCAL POLICY OF THE USA - Ameer S. Muhammed; Dr. Mohamed S. Mohamed (QALAAI ZANIST JOURNAL, 2019)
This study aimed to evaluate the impact of the financial crisis of 2008 on the fiscal policy of the USA from 2004 to 2012. The study found that this crisis had a significant effect on the USA fiscal policy. More clearly, the USA budget balance as an indicator of fiscal policy and its structural budget balance as an indicator of discretionary fiscal policy had changed seriously during this period. The study also reveals that during the years (2007-2012), the USA government used a countercyclical and an expansionary fiscal policy as a whole and as discretionary measures. To face such crisis and mitigate its effects, the study recommends that with the using of the fiscal policy and discretionary measures, it is better for the USA government to activate automatic stabilizers measures. In addition, to use other policies especially monetary policy and with the fiscal policy in the same direction.